PENGELOLAAN INTERNET DALAM MEWUJUDKAN DESA BROADBAND TERPADU DI DESA WONOSARI KABUPATEN BENGKALIS - Al Imami "; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Wonosari is a village in Bengkalis district who get free internet facility, or better known as integrated broadband villages.Integrated broadaband village (DBT) is a government program to help villages with certain characteristics such as fishing villages, farming villages and remote villages to optimize the information and communications technology in the region. The central government through the ministry of communications and information technology related to the program responsible for this integrated broadband village. The purpose of this study was to determine thesystem management and use of the Internet in realizing Rural Broadband in Wonosari Bengkalis.This study uses descriptive qualitative research. This research was conducted at the Head Office of Wonosari Bengkalis. Selection of informants by using purposive. Data collection techniques used for this research is by interview, observation and documentation. Meanwhile, data validity checking techniques that researchers use is an extension of participation and triangulation.The results showed in the management of rural broadband internet use management system by utilizing human resources, method, money, and machine. In managing this broadband village guided by three admin manager, ie as a data penginput village, journalists or search information about the village, and part of the public service. Broadband internet management process carried out through four stages: Planning, Organizing, Actuating, and Controlling. For Internet use village is divided into three areas of utilization. The first field of the economy, local communities use the internet through a broadband rural village official website to promote their business results such as farming of pineapple and dragon fruit. The second field of education, the local community, especially students villages broadband network utilizing the Internet to look for references of their college assignments. And the third field of business, one of the benefits of broadband internet in this area is the village they can make buying and selling online.